NURSING CARE FOR DIABETES MELLITUS WITH SKIN INTEGRITY CARE INTERVENTION ON JAMBI CITYMRS. M IN THE TRIBUTE ROOM H. ABDUL MANAP REGIONAL HOSPITAL, - Nurhusna; Gani, Alda Afrila (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
Hyperglycemia chronic in diabetes mellitus results in nerve disorder​ as well as happen damage integrity skin / tissue. Prevention disturbance integrity skin is very important with non- pharmacological therapy considered more safe than modern medicine. One of intervention maintenance integrity skin with therapy massage technique effluent massage with Virgin Coconut Oil (VCO)/ oil which olive is technique to wipe very or twice a day effective in prevent damage integrity skin. Purpose study This For know care diabetes mellitus nursing with intervention maintenance integrity skin on Mrs. M in the room paper at H. Abdul Manap Regional Hospital, Jambi City. Methods used​ in study This is studies case. Samples taken in study This is a with problem disturbance integrity Diabetes Mellitus skin. Research data This taken with use method observation participatory, interview No structure, and documentation. Research result obtained that maintenance integrity skin with use effluent massage with oil olive / VCO can in the case of diabetes mellitus in Mrs. M showed repair. Repair symptoms that can observed among others obtained reddish decreased, temperature skin improved and texture get better as well as damage layer skin get better. Care diabetes mellitus nursing with intervention maintenance integrity skin on Mrs. M in the room The paper from H. Abdul Manap Regional Hospital, Jambi City was obtained results existence repair symptoms that can observed among others obtained reddish decreased, temperature skin improved and texture get better as well as damage layer skin get better. It is expected to party House Sick For can use Evidence based ( massage efflurage with VCO/ oil administration olives,) as action independent and develop it in increase maintenance integrity skin in patients with diabetes mellitus.